How patients experience nurse-doctor collaborative care at specialist clinics: A qualitative study - Yang Yann Foo; Xiaohui Xin; Qianhui Cheng; Hwee Kuan Ong; Ting Ting Yeoh; Wentao Zhou; Siti Rohaida Rahmat; Nigel C.K. Tan; Jai Rao; Kirsty J. Freeman; Sok Mui Lim; Kevin Tan (PLoS ONE, 2025)
Introduction Patient experience of interprofessional collaboration in primary care has been well-studied but not in specialist clinics. Our qualitative study aimed to understand patients’ experience of a nurse-doctor collaboration at three specialist clinics (Epilepsy Clinic, Neuroimmunology Clinic, and Persistent Concussion Clinic) in a tertiary neurology care centre in Singapore. Methodology Between December 2023 and April 2024, participants of different demographic and disease profiles from the three specialist clinics were recruited using maximum variation selection. We generated observation and interview data to understand patient experience in a multifaceted and in-depth manner. We analyzed the data using Braun and Clarke’s reflexive thematic analysis. Results We observed 27 patients, of whom 12 agreed to be interviewed. We constructed two themes. The first discussed the patients’ varied receptivity to interprofessional collaboration depending on their perceived healthcare needs. Most patients valued collaborative care as it saved time and enhanced their access to psychosocial and financial support. However, patients whose disease status was still active preferred to consult the doctors for symptomatic management through drug treatment. They were observed to be reticent about sharing their preference with the care team. The second theme examined the absence of formal introduction of the concept of interprofessional collaboration to the patients. Some patients appeared to be unaware that specialist nurses were qualified to collaborate with doctors, and this lowered their perceptions of the nurses’ competence and seemingly weakened their receptivity to IPC. Conclusion Patients’ experience of IPC at specialist clinics varied depending on patients’ perceived healthcare needs. To optimize patients’ receptivity to IPC, the provision of collaborative care should be calibrated to fulfill different patients’ perceived and actual healthcare needs. Doing so may optimize the value of collaborative care to patients. Further enhancements to patients’ receptivity would involve the intentional effort to prepare patients for collaborative practice.